Legal Issues in Handling Breach of Contract in Commercial Agreements (A Study on Law No. 8 of 1999 Concerning Consumer Protection) - Khairun Naim; Sri Wenti Buulolo; Yohanes Herman Buulolo; Sonotehe Halawa; Yaniman Gulo (Yayasan Multidimensi Kreatif, 2026)
In commercial transactions, breach of contract (wanprestasi) remains a significant legal issue that can disrupt business relations and cause financial losses. This study aims to analyze legal problems in handling wanprestasi in trade contracts and examine the obligations and rights of parties under Law No. 8 of 1999 concerning Consumer Protection. The research method used is normative juridical, involving the examination of statutory regulations, case law, and other legal materials relevant to commercial contracts and breaches. The findings indicate that wanprestasi often occurs due to delayed performance, non-conformity of goods or services, and failure to fulfill contractual obligations. Legal remedies include claims for compensation, contract termination, and dispute resolution through litigation or alternative mechanisms such as arbitration. The discussion highlights challenges in enforcing contractual rights, particularly regarding clarity of obligations and effectiveness of existing regulations. The study concludes that understanding legal provisions and strengthening contractual agreements are crucial to mitigate risks of wanprestasi in trade transactions.